Kyai Sadrach Dan Gerakan Pribumisasi Kristen Di Jawa - Lukas Kadimin (Jurnal Silih Asuh : Teologi dan Misi, 2024)
This research will discuss the historical issue of the beginning of the Christian indigenization movement in Java up to its development. This was done in response to the Dutch colonial era zending (Western evangelists) who did not care about Javanese culture. Kyai Sadrach, an indigenous evangelist, made a major contribution to the indigenization movement in Java. His ministry was very successful in forming a Christian community in Java. He had started to establish a church whose congregation was native people and grew very rapidly in his time. By the end of his life, Kyai Sadrach's congregation had reached 20,000 members (1869-1823). Kyai Sadrach focuses on services to rural communities. The strategy used is a cultural contextual approach and local customary procedures, especially those related to Islamic customs, so that it gets good acceptance. Therefore, this research was created to provide an understanding of the Christian indigenization movement in Java and how big the influence of Kyai Sadrach was in this movement. The sources used to write this paper are books and articles and digital material sources related to the discussion of the History of Christianity in Java.